Three Generations of Haji Noor Ali Sowdagar and Sons Limited: SWOT Analysis of a Family Business (Global Journal of Management and Business Research, 2020)
The purpose of this study is to discover the factors that lead to sustaining a business for three generations from the early 20th century to the 21st century. For this purpose, this study used a SWOT model and identified internal strengths and weaknesses; and external threats and opportunities of the Haji Noor Ali Sowdagar and Sons Limited, which is a soap manufacturing enterprise established in the port city of Chittagong, Bangladesh. The study reveals goodwill as the enterprise's key strength while lacking of dynamic management as the major weakness. This study also found growing local competition as the main threat while expanding demand as the major opportunity for the enterprise. This study concluded that Haji Noor Ali Sowdagar and Sons Limited lacks a proper segmentation, targeting and positioning strategy and needs to revaluate it's 'one size fits all' approach to adapt to the changing and expanding demand of the country.
Keywords: SWOT; 1937 saban; haji noor ali sowdagar